2013
DOI: 10.1007/s00381-013-2268-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of the gene expression and microRNA expression profiles of malignant rhabdoid tumors originated in the brain (AT/RT) and in the kidney (RTK)

Abstract: Based on our results, we hypothesized that although MRT are indeed the same tumor, independent of the site of origin, the GE differences reflect the influence of microenvironment over tumor development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…To assess whether our MRT sub-groups were more similar to AT/RT or to RTK, we used data from Grupenmacher et al (2013), which analyzed gene expression differences between AT/RT and RTK. We compared the genes differentially expressed between MRT sub-groups to 29 genes reported by Grupenmacher et al (2013) as over-expressed in AT/RT relative to RTK (Table S4). Of these, 11 were differentially expressed between MRT subgroups 1 and 2 (FDR < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess whether our MRT sub-groups were more similar to AT/RT or to RTK, we used data from Grupenmacher et al (2013), which analyzed gene expression differences between AT/RT and RTK. We compared the genes differentially expressed between MRT sub-groups to 29 genes reported by Grupenmacher et al (2013) as over-expressed in AT/RT relative to RTK (Table S4). Of these, 11 were differentially expressed between MRT subgroups 1 and 2 (FDR < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…10 of the 11 genes were over-expressed in subgroup 1 (Table S4), including genes linked to neuronal differentiation (e.g., BEX1 , FAM5C/BRINP3; Coyle et al, 2011; Terashima et al, 2010; Vilar et al, 2006) or neural crest differentiation (e.g., ENC1; Rabadán et al, 2013). Conversely, of the 92 genes reported (Grupenmacher et al, 2013) as over-expressed in RTK relative to AT/RT, 21 were differentially expressed between sub-group 1 and 2, and all were over-expressed in sub-group 2 (one-sided Fisher’s exact p value = 1.193e-13; Table S4). These results are compatible with the notion that MRT sub-group 1 may be more similar to AT/RT, and MRT sub-group 2 may be more similar to RTK.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs are directly involved in the changes that the brain microenvironment implies on the metastatic tumor cells as many studies have shown that the brain microenvironment change the miRNA profile of the tumor cells when compared with the primary tumor. Rhabdoid tumor cells showed different miRNA profiles when originated in the brain compared to the kidney [52]. MiRNA-146a was noted to be suppressed in brain metastases compared to the original tumors in animal models, associated with decreased β-catenin protein levels and increased heterogeneous nuclear ribonucleoprotein C1/C2 (hnRNPC) which may increase migratory and invasive capabilities [48].…”
Section: Mirnas and Brain Metastasesmentioning
confidence: 99%
“…They can arise at any anatomical location and their cell of origin is unknown. The most common site of origin is the central nervous system (CNS) where they are known as atypical teratoid/rhabdoid tumors (AT/RT) [1]. According to recent data from the German Childhood Cancer Registry, it is estimated that AT/RTs make up to 65% of all rhabdoid tumors, while 5-10% are originated in the kidneys and are called rhabdoid tumors of the kidney or RTK.…”
Section: Introductionmentioning
confidence: 99%